Qualitative exploration of health system response to COVID-19 pandemic applying the WHO health systems framework: Case study of a Nigerian state (2021)
Pandemics can result in significantly high rates of morbidity and mortality with higher impact in Lower- and Middle-Income Countries like Nigeria. Health systems have an im-portant role in a multi-sector response to pandemics, as there are already concerns that COVID-19 will significantly divert limited health care resources. This study appraised the readiness and resilience of the Nigerian health system to the COVID-19 pandemic, using Oyo State, southwest Nigeria, as a case study. This study was a cross-sectional qualita-tive study involving key informant and in-depth interviews. Purposive sampling was used in recruiting participants who were members of the Task Force on COVID-19 in the state and Emergency Operations Centre (EOC) members (physicians, nurses, laboratory scientists, “contact tracers”, logistic managers) and other partners. The state’s health system response to COVID 19 was assessed using the WHO health systems framework. Audio recordings of the interviews done in English were transcribed and thematic analysis of these tran-scripts was carried out using NVIVO software. Results show that the state government re-sponded promptly by putting in place measures to address the COVID-19 pandemic. How-ever, the response was not adequate owing to the fact that the health system has already been weakened by various challenges like poor funding of the health system, shortage of human resources and inadequate infrastructure. These contributed to the health system’s sub-optimal response to the pandemic. In order to arm the health system for adequate and appropriate response during major health disasters like pandemics, fundamental pillars of the health system-finance, human resources, information and technology, medical equip-ment and leadership - need to be addressed in order to have a resilient health system.